2017
DOI: 10.3389/fspas.2017.00009
|View full text |Cite
|
Sign up to set email alerts
|

A Catalog of Active Galactic Nuclei from the First 1.5 Gyr of the Universe

Abstract: Active galactic nuclei (AGN) are prominent astrophysical objects that can be observed throughout the whole Universe. To understand the underlying physical processes and the different appearance of AGN types, extensive samples are needed. Nowadays, various AGN catalogs are available at different wavebands. However, at the highest redshifts data are still relatively sparse. These data are required for examining AGN properties in the early Universe. This way we can compare the earliest AGN with those seen at lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…The fact that only ∼ 10% of the optically detected quasars are radio-loud, and that radio-loud quasars become too weak to be detected by radio telescopes at very large cosmological distances make high-redshift radio-loud quasars much more rare. The number of radio-detected AGNs with available spectroscopic redshift at z > 4 is only about 170 [7], and the most distant radio-loud quasar to date is J1429+5447 at z = 6.21 [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that only ∼ 10% of the optically detected quasars are radio-loud, and that radio-loud quasars become too weak to be detected by radio telescopes at very large cosmological distances make high-redshift radio-loud quasars much more rare. The number of radio-detected AGNs with available spectroscopic redshift at z > 4 is only about 170 [7], and the most distant radio-loud quasar to date is J1429+5447 at z = 6.21 [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of the first quasar at redshift z ≥ 4 (Warren et al 1987), the number of active galactic nuclei (AGN) known at the highest redshifts is continuously increasing. As a result of extensive observing campaigns and surveys (e.g., York et al 2000;Wright et al 2010;Eisenstein et al 2011;Chambers et al 2016;Dark Energy Survey Collaboration et al 2016;Blanton et al 2017), there are nearly 3000 sources identified between z = 4 and z = 7.54 to date, yet only ∼ 6.5 per cent of these exhibit radio emission (Perger et al 2017) detected at 1.4 GHz by either the Very Large Array (VLA) Faint Images of the Radio Sky at Twenty-Centimeters 1 (FIRST, Becker, White & Helfand 1995;Helfand, White & Becker 2015) survey or the National Radio Astronomy Observatory (NRAO) VLA Sky Survey 2 (NVSS, Condon et al 1998). The remaining sources are either outside the footprint of ⋆ E-mail: k.perger@astro.elte.hu 1 http://sundog.stsci.edu/ 2 https://www.cv.nrao.edu/nvss/ both FIRST and NVSS, or are below the detection limit of the two surveys.…”
Section: Introductionmentioning
confidence: 99%
“…They are also rare because of the limited sensitivity of our instruments. For example, the number of known AGN with measured spectroscopic redshift at z > 4 is nearly 2600, and only about 170 are known radio sources (Perger et al 2017). In comparison, the total number of AGN is now close to a million (Flesh 2015).…”
Section: Introductionmentioning
confidence: 99%